Allelic variants of breast cancer susceptibility genes PALB2 and RECQL in the Latvian population - Philip Hilz; Reicela Heinrihsone; Lukas Alexander Pätzold; Qi Qi; Genadijs Trofimovics; Linda Gailite; Arvids Irmejs; Janis Gardovskis; Edvins Miklasevics; Zanda Daneberga (Hereditary Cancer in Clinical Practice, 2019)
Abstract Background Large-scale case control studies revealed a number of moderate risk - low frequency breast cancer alleles of the PALB2 and RECQL genes. Some of these were reported as founder variants of Central and Eastern Europe. Based on highly similar founder variant spectra of the BRCA1 in Poland and Latvia, we decided to test the frequency of other common variants of moderate breast cancer risk — c.509_510delGA (rs515726124) and c.172_175delTTGT (rs180177143) of the PALB2 gene and c.1667_1667+3delAGTA variant of the RECQL gene in a breast cancer case-control series from Latvia to better understand the role of genes in susceptibility to breast cancer and their clinical significance. Methods The case-control study was performed based on an unselected breast cancer case group of 2480 women and a control group, including 1240 voluntary, to our knowledge unrelated, female donors without reported oncological disease. Results The calculated frequency for c.509_510delGA of the PALB2 gene in the case group is 0.35 and 0.00% in the control group, with respective relative risk (RR) 7.18 (CI 95% 0.37–138.75; p = 0.19). As for the PALB2 c.172_175delTTGT variant, the frequency in the case group of our study is 0.04%. In the control group of our study all individuals were homozygous for the wild-type allele, which lead to calculated RR = 1.50 (CI 95% 0.06–36.83; p-value = 0.80). There were no carriers of the RECQL variant c.1667_1667+3delAGTA identified in our case group and 2 heterozygotes were identified in the control group. The calculated RR = 0.26 (CI 95% 0.01–5.33; p-value = 0.38). Conclusion Results obtained for the PALB2 gene variants are able to supplement evidence on the allele frequency in breast cancer patients from the region of Central and Eastern Europe. Based on our results we cannot confirm the contribution of the RECQL variant c.1667_1667+3delAGTA allele to breast cancer development.